Psychiatric Symptoms in a Patient with NMDA Receptor Encephalitis: Psychiatric Symptoms in a Patient with NMDA Receptor Encephalitis - Paudel, L; Samadarshi, S; Limbu, S; Sharma, R; Chalise, P; Pradhan, SN (Journal of Psychiatrists' Association of Nepal, 2020)
Anti N methyl D aspartate receptor (NMDA-R) encephalitis is an autoimmune disorder that encompasses various psychiatric and neurological symptoms. Psychiatric manifestations are often the presentation of the disease that often delay or mislead the diagnosis. Complex psychiatric symptoms, seizures, autonomic instability, abnormal movements, behavioral changes and impaired cognitive functions are present during the course of illness. Prodromal psychiatric symptoms often confuse the physicians and even patient initially seeks psychiatric consultation. Here we present a case of 19 years female who presented with initial psychiatric symptoms that progressed to seizure, autonomic instability, abnormal movement and other encephalitic symptoms.